2020
DOI: 10.3389/fonc.2020.00855
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Non-Small Cell Lung Cancer by Using a 12-microRNA Panel and a Nomogram for Assistant Diagnosis

Abstract: Background: We previously identified a 12-microRNA (miRNA) panel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…CTCs in the blood could serve as effective screening and diagnostic markers to discriminate small malignant pulmonary nodules from benign lesions [ 54 , 56 ]. The profiling of circulating microRNAs has promising accuracy for discriminating lung cancer patients from healthy controls and could be developed as a supplement in future screening [ 51 , 84 ]. Recently, integrative multi-analytical models combining clinical features and multiple biomarkers have achieved a better balance of predictive sensitivity and specificity [ 16 , 40 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…CTCs in the blood could serve as effective screening and diagnostic markers to discriminate small malignant pulmonary nodules from benign lesions [ 54 , 56 ]. The profiling of circulating microRNAs has promising accuracy for discriminating lung cancer patients from healthy controls and could be developed as a supplement in future screening [ 51 , 84 ]. Recently, integrative multi-analytical models combining clinical features and multiple biomarkers have achieved a better balance of predictive sensitivity and specificity [ 16 , 40 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC patients, miR-221 levels increase significantly in plasma, suggesting its potential as a therapeutic target or non-invasive marker for early diagnosis and screening of NSCLC [ 214 ]. Wang et al (2020) also suggested miR-221 as one of the biomarkers for early detection of NSCLC [ 215 ].…”
Section: Tumor Enhancer Mirnamentioning
confidence: 99%
“…To date, several important miRNAs have been identified for regulating muscle growth and development, such as miR-205, miR-126, miR-60, miR-75, miR-133, miR-499, etc. [ 2 ]. MyoD1 , a marker gene of muscle differentiation, is regulated by miR-1 and miR-206 [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%